The Emperor Has No Clothes! Unanswered Questions and Concerns on the Response To Intervention Procedure - Baskette, Michael R.; Ulmer, Lisa; Bender, William N. (Journal of the American Academy of Special Education Professionals, 2006)
Recent legislation offers the option of using a response to intervention (RTI) procedure for documenting a learning disability. While we generally support the use of response to intervention procedures for eligibility determinations, there are many unanswered questions on implementation of this procedure as well as some question as to the overall efficacy of this procedure when used as an eligibility tool. This article presents many of these issues, and suggests our recommendations as to the possible solutions.